STRATEGI MODAL ‘ALA AL-ASWANY DALAM ARENA SASTRA ARAB: KAJIAN SOSIOLOGI SASTRA PIERRE BOURDIEU - Asih, Kusuma Dewi; Anum, Rahning Asri (Afshaha: Jurnal Bahasa dan Sastra Arab, 2023)
'Ala Al-Aswany is one of the modern Arab writers. His name is well-known among Arab writers, and his works are accepted, enjoyed, and studied by critics, even receiving numerous awards. This research aims to analyze the capital strategies employed by 'Ala Al-Aswany to obtain his position or legitimacy in the Arab literary arena using Pierre Bourdieu's sociology of literature. This study is a qualitative research with a descriptive-analytical method, using data sources such as books, articles, research reports, and other documents related to the topic and theory used. The data collection technique is documentation. The data is analyzed by identifying the author's biography and his contributions to the Arab literary world, then formulated and described relationally based on Pierre Bourdieu's capital structure. The results show that Al-Aswany possesses four types of capital classified from Pierre Bourdieu's perspective: economic, cultural, social, and symbolic capital. With the arena of production and these four capital strategies, he achieves a specific legitimacy, in this case, Al-Aswany attains the position of a "specific writer" in the Arab literary arena.